Voice changes after thyroidectomy: an experience with 364 cases of thyroid surgery - Prabhat, Arvind K.; Dash, Niranjan; Gadekar, J. M. (International Surgery Journal, 2018)
Background: To study voice changes and to evaluate the impact of thyroidectomy and effects of factors such as patient age, sex, operation-type, surgeons-experience, laryngeal nerve injury and orotracheal intubation on voice of patients undergoing thyroidectomy. Methods: Author prospectively analyzed 364 cases of multinodular goiter (MNG) and neoplastic thyroid disorders, undergoing sub-total/total-thyroidectomy and completion-thyroidectomy in the department of surgery, during the study period of June 2016 to December 2016. Results: The study comprised of 364 patients, with 298 females and 66 males. Voice changes were seen in 216(59.34%) patients. Transient voice changes were seen in 212(98.15%) patients and permanent in 4(1.85%) patents. Out of 216 patents, age group ≥65 years were 128(59.25%) and age group <65 years were 88(40.75%) patients(p:0.012324). Out of 216 patients in which voice changes were seen,165(76.39%) patients were females and 51(23.61%) patients were males(p:0.001046). Voice changes were seen in 190(88%) patients in which sub-total/total-thyroidectomies were performed and in 26(12%) patients completion-thyroidectomies were performed. Voice changes were statistically significant in which completion-thyroidectomies were performed(p:0.002102). Voice changes were seen in 205(68.56%) cases and 11(16.92%) cases which were performed by post-graduate-trainee and experienced-surgeon respectively. Voice changes were seen in 122(67.77%) cases in which orotracheal intubation was performed and in 94(51.65%) cases cervical-epidural anaesthesia was given (p:0.00281). RLN palsy was seen in 2(0.60%) cases in which sub-total/total-thyroidectomy were performed and 2(6.25%) cases in which completion-thyroidectomy was performed (p:0.003426). Conclusions: Voice changes is common after thyroid surgery but usually transient and sometimes, permanent. So, patients must be informed about the risk of voice-impairment after thyroid surgery. Present study is novel as it investigates not only laryngeal neve injury but also highlights patient age, sex, types of operation, surgeons experience and laryngeal complications during orotracheal intubation.